A Case of Blood Group A2B with Anti A1 Antibody Reactive at 37°C (Bangladesh Journal of Medicine, 2022)
Landsteiner discovered ABO blood group system. It is most important for transfusion medicine. Blood group A has several subtypes and most important are A1 and A2, upon which further groups of A and AB have been classified as A1, A2 and A1B, A2B. Of individuals with A antigen, approximately 20% belong to A2 while rest 80% belong to A1. Anti-A1 Lectin, a cold agglutinin which destroys A1 cells is clinically significant when they react at 37°C, causing transfusion reactions.Bangladesh J Medicine 2022; 33: 312-316